HLA-B*57 versus HLA-B*81 in HIV-1 infection: Slow and steady wins the race? - Prentice, H; Porter, T; Price, M; Cormier, E; He, D; Farmer, P; Kamali, A; Karita, E; Lakhi, S; Sanders, E; Anzala, O; Amornkul, P; et al. (American Society for Microbiology, 2013)
Two human leukocyte antigen (HLA) variants, HLA-B*57 and -B*81, are consistently known as favorable host factors in human immunodeficiency virus type 1 (HIV-1)-infected Africans and African-Americans. In our analyses of prospective data from 538 recent HIV-1 seroconverters and cross-sectional data from 292 subjects with unknown duration of infection, HLA-B*57 (mostly B*57:03) and -B*81 (exclusively B*81:01) had mostly discordant associations with virologic and immunologic manifestations before antiretroviral therapy. Specifically, relatively low viral load (VL) in HLA-B*57-positive subjects (P ≤ 0.03 in various models) did not translate to early advantage in CD4+ T-cell (CD4) counts (P ≥ 0.37). In contrast, individuals with HLA-B*81 showed little deviation from the normal set point VL (P > 0.18) while maintaining high CD4 count during early and chronic infection (P = 0.01). These observations suggest that discordance between VL and CD4 count can occur in the presence of certain HLA alleles and that effective control of HIV-1 viremia is not always a prerequisite for favorable prognosis (delayed immunodeficiency). Of note, steady CD4 count associated with HLA-B*81 in HIV-1-infected Africans may depend on the country of origin, as observations differed slightly between subgroups enrolled in southern Africa (Zambia) and eastern Africa (Kenya, Rwanda, and Uganda).